PREDICTORS OF OUTCOME FOLLOWING ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION: A PROSPECTIVE COHORT STUDY IN UK SPORTS MEDICINE. (19th July 2019) - Neal, Bradley Stephen; Miller, Stuart; Small, Claire; Lack, Simon David
No abstract available